Analysis of Strength Parameters of Polymer–Glass Composites Modified with Rubber Recyclate Through Bending Tests - Daria Żuk (International Journal of Engineering and Technology Innovation, 2024)
The study aims to analyze the strength properties obtained from three-point bending tests of epoxy-glass composite samples modified by adding rubber recyclate. A pure epoxy-glass composite is used as a comparative variant. The tested materials, which varies in the percentage of rubber recyclate and distribution, are cut through waterjet cutting to minimize the influence of temperature. The results undergo statistical analysis, and the microstructures are examined using scanning electron microscopy. The decreasing bending strength of the composites is observed, as the content of rubber recyclate in the material increased. However, adding rubber recyclate directly into the resin subtly decreases in bending strength compared to adding in the layers between the glass mat layers. Composites with rubber recyclate exhibits lower deflection under load compared to pure composites. The most favorable bending test parameters are obtained for the material containing 5% rubber recyclate distributed in three layers.